2006
DOI: 10.1107/s0907444906035712
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on peanut lectin complexed with disaccharides involving different linkages: further insights into the structure and interactions of the lectin

Abstract: Crystal structures of peanut lectin complexed with Galbeta1-3Gal, methyl-T-antigen, Galbeta1-6GalNAc, Galalpha1-3Gal and Galalpha1-6Glc and that of a crystal grown in the presence of Galalpha1-3Galbeta1-4Gal have been determined using data collected at 100 K. The use of water bridges as a strategy for generating carbohydrate specificity was previously deduced from the complexes of the lectin with lactose (Galbeta1-4Glc) and T-antigen (Galbeta1-3GalNAc). This has been confirmed by the analysis of the complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…For example, it is recently reported that the antitumor galectin AAL recognizes its bioactive ligand, the TF antigen, by using a Glu-Water-Arg-Water motif [15]. The peanut lectin employs the water bridges for generating carbohydrate specificity [16]. Diego et al, also reported that water molecules on the surface of the carbohydrate recognition domain of galectins were related to the galectins' affinity for carbohydrate ligand recognition [17].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is recently reported that the antitumor galectin AAL recognizes its bioactive ligand, the TF antigen, by using a Glu-Water-Arg-Water motif [15]. The peanut lectin employs the water bridges for generating carbohydrate specificity [16]. Diego et al, also reported that water molecules on the surface of the carbohydrate recognition domain of galectins were related to the galectins' affinity for carbohydrate ligand recognition [17].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, lectins using water molecules to recognize the carbohydrate is frequently observed. For example, the peanut lectin employs the water bridges for generating carbohydrate specificity (26). Diego et al .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, lectins using water molecules to recognize the carbohydrate is frequently observed. For example, the peanut lectin employs the water bridges for generating carbohydrate specificity (26). Diego et al (27) also reported that water molecules on the surface of the carbohydrate recognition domain of galectins were related to the galectins' affinity for carbohydrate ligand recognition.…”
Section: Aal-tf Recognitionmentioning
confidence: 99%
“…The three two-fold axes combine to give rise to an irrational screw axis, Q, perpendicular to all of them and relates C to A (146°, 24 Å) and D to B (-146°, -24 Å). Repeated occurrence of the same quaternary structure in crystal forms of the lectin grown under widely different conditions [17][18][19][20][21][22][23][24] demonstrates that the observed open conformation is not an artefact of crystallization. Solution studies also showed that PNA is a tetramer and that the tetrameric association in it is perhaps stronger than that in well known tetrameric proteins like ConA and hemoglobin.…”
Section: Unusual Quaternary Structure and Variability In Quaternary Amentioning
confidence: 99%
“…PNA-sugar interactions have been investigated through the X-ray analysis of a number complexes with carbohydrates including a number of disaccharides with different glycosidic linkages between the monosaccharide residues [17][18][19][20][21][22][23]. The interactions involve four binding loops, residues 75-83, 91-106, 125-135 and 211-216 in all of them.…”
Section: Lectin-sugar Interactions Generation Of Ligand Specificity mentioning
confidence: 99%